Empreendedorismo feminino no Brasil: uma visão a partir da influência da orientação empreendedora individual e das capacidades dinâmicas no desempenho organizacional - Silva, Ana Carolina Cozza Josende da (2025)
Female entrepreneurship represents a global socio-economic pillar, driving development and empowerment, especially in emerging markets such as Brazil. Despite its relevance, the literature lacks an integrated understanding of the factors that determine the success of women's entrepreneurial organisations. To fill this gap, Individual Entrepreneurial Orientation (IEO) and Dynamic Capabilities (DCs) emerge as essential constructs to explain business performance. IEO encompasses the entrepreneurial attributes and personal behaviours of an individual, while DCs represent an organisation's ability to adapt, integrate, and reconfigure its competencies. Thus, the general objective was to analyse how individual entrepreneurial orientation and dynamic capabilities influence the performance of women's entrepreneurial organisations in Brazil. The specific objectives included: identifying the profile of women and women's entrepreneurial organisations in Brazil; verifying the influence of IEO on organisational performance (OP) in Brazilian women's entrepreneurial organisations; verifying the influence of IEO on DCs in Brazilian women's entrepreneurial organisations; verifying the influence of DCs on OP in Brazilian women's entrepreneurial organisations; examining the mediating role of DCs in the relationship between IEO and OP; and testing the effects of perceived environmental uncertainty (EU) on IEO, DCs, and OP. The theoretical framework encompasses female entrepreneurship, IEO (innovation, proactiveness, risk-taking propensity, passion, perseverance), DCs (absorptive, adaptive, innovative), OP (financial and non-financial), and EU (dynamism, complexity, munificence). The methodology adopted an exploratory, descriptive, and quantitative approach, using a survey. Data collection was conducted through a structured questionnaire with 377 Brazilian women entrepreneurs, using non-probabilistic convenience sampling. Data analysis employed descriptive statistics, confirmatory factor analysis, and structural equation modelling using SmartPLS software. The results revealed a profile of mature entrepreneurs, with high educational attainment, mothers, operating in micro and small service businesses. All main hypotheses of the proposed model were supported, evidencing the validity of the interactions between the constructs, where IEO positively influences OP and DCs; DCs positively influence OP; and DCs mediate the relationship between IEO and OP. A decisive finding is that EU directly influences IEO, but not DCs or OP directly. IEO acts as a full mediator of EU on DCs and OP. The results indicate that IEO is a central mechanism for entrepreneurs to respond to environmental uncertainty, driving capabilities and organisational performance.